Determination of efficacy of pre-procedural mouth rinsing in reducing aerosol contamination produced by ultrasonic scalers - Rao, Reema M.; Shenoy, Nina; Shetty, Veena (Journal of Health and Allied Sciences NU, 2015)
The oral cavity is a unique environment which can provide an ideal medium for bacterial growth. Most of the procedures performed by dentist have the potential for creating contaminated aerosols and splatter which contains bacteria, fungi, protozoa and even blood borne viruses produced during dental operative procedures and thus promoting an increased risk of cross infection. In dentistry, the ultrasonic scaler and the air polisher are considered to be the greatest producers of small particle aerosol contamination. Aerosols can remain airborne for extended periods of time and may be inhaled and was also found that the microorganisms could survive in the aerosol produced for as long as 6 days. The association of these aerosols with the respiratory infections, opthalamic and skin infections, tuberculosis and hepatitis B have been reported.Chlorhexidine is considered as the “Gold standard” of antimicrobial rinse because of broad-spectrum antibacterial activity and substantivity of 8-12 hrs. This study determined the efficacy of preprocedural rinsing with an antimicrobial mouthrinse containing chlorhexidine in reducing the level of viable bacteria contained in aerosols generated by ultrasonic scaling.The results of the present study clearly indicate that pre-procedural mouth rinse with 0.2% chlorhexidine gluconate was significantly effective in reducing the aerosol contamination during use of ultrasonic scaling in dental practice Using a pre-procedural rinse can significantly reduce the viable microbial content of dental aerosols.
Keywords: Aerosols; ultrasonic scaling; colony forming units